2-[(1E,3E)-4-Arylbuta-1,3-dien-1-yl]-4H-chromen-4-ones as dienes in Diels–Alder reactions: experimental and computational studies - Albuquerque, Hélio (2017)
The synthesis and reactivity of 2-[(1 £,3£)-4-arylbuta-1 ,3-dien-l-yl]-4H-chromen-4-ones 1 as dienes in Diets-Alder (DA) reactions towards several electron-poor and electron-rich dienophiles under microwave irradiation was studied. The optimized reaction conditions were achieved by using N-methylmaleimide2 as dienophile and Sc(0Tf)3 as Lewis acid under microwave-assisted and solvent-free conditions. The Lewis acid improved the reaction yields since it prevented the adducts obtained to undergo a second DA reaction, thus avoiding formation of a bisadduct. The a,~:y ,o-diene of the starting chromones showed to be the most reactive and the computational results confirmed the experimental findings. Theoretical calculations also allowed explaining some unexpected lack of reactivity by some dienophiles. The adducts prepared were dehydrogenated by using DDQ, however, the aza-adducts showed to be sensitive to the high energetic reaction conditions necessary to perform the aromatization.